Holistic health in ageing: A multifaceted approach to diet, habits and mental health from the Malaysian perspective - Sadia Choudhury Shimmi; Md Sayed Uddin; Mazlinda Musa (Penerbit Universiti Malaysia Sabah, 2024)
Ageing is a significant challenge for both developing and developed countries today. The life expectancy of older adults is increasing due to advanced healthcare facilities and health education. Malaysia is projected to have 14% of its population over the age of 60 by 2030, with this figure expected to rise to 24% by 2050. In 2023, the population of individuals over 60 years old had increased to 3.8 million, according to the Malaysian Department of Statistics. This growing trend will create a burden on the country, requiring it to provide optimum healthcare systems and healthcare expenditure continuously. For ageing people, lack of knowledge about healthy diets and availability as well as the timing of food taking is one of the important concerns for their nutrition. These ageing people have no assistance in taking medication on time, which is another major concern about their physical inactivity. The older c sensations may change or changing recognition threshold, which may lead to nutritional deficiencies. Physical activities, smoking, alcohol or other habits maintain inappropriate ways and not performing physical activities because of several factors is another factor. Again, mental health is a very big issue to maintain a healthy lifestyle. As a result, older people need to remain physically active, maintain healthy personal habits and have regular medical checkups. In addition, a proper balance of diet and nutrition is crucial to prevent chronic health complications and reduce the need for frequent hospitalization. Furthermore, attention should be given to their mental health condition, as mental health is related to physical disabilities. This comprehensive approach can support the adoption of a healthier lifestyle. Again, regular follow-ups at least twice a year up to their life expectancy can maintain their health both physically and mentally. Therefore, this holistic approach to overall health data is essential for improving and enhancing healthy life expectancy and quality of life.